2013
DOI: 10.1097/mph.0b013e318271f43f
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Modified St Jude Total Therapy 13A for Childhood Acute Lymphoblastic Leukemia in the Southeast Region of Turkey

Abstract: St Jude Total 13A treatment protocols to treat childhood ALL can be successfully adapted, which suggests that such an approach may be useful in low socioeconomic regions; however, it should be noted that secondary leukemia can occur at a high rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 30 publications
2
9
2
Order By: Relevance
“…In the study by Dujua and Hernandez (16) from the Philippines, the rate of male ALL cases was found to be 61.5%. In some studies conducted in our country, ALL was reported to be more common in male, while in some studies, it was reported to be more common in female (17,18). In our study, 86 of the 129 patients (66%) were male, 43 (33%) were girls and the male/female ratio was 2/1.…”
Section: Discussionsupporting
confidence: 43%
“…In the study by Dujua and Hernandez (16) from the Philippines, the rate of male ALL cases was found to be 61.5%. In some studies conducted in our country, ALL was reported to be more common in male, while in some studies, it was reported to be more common in female (17,18). In our study, 86 of the 129 patients (66%) were male, 43 (33%) were girls and the male/female ratio was 2/1.…”
Section: Discussionsupporting
confidence: 43%
“…In Turkey, a similar Total XIII protocol was adopted and the 5‐year EFS was 77%. The induction death was 12.3% and infection was the most important cause of death . In India, septicemia was also reported to be an important cause of death, accounting for 29.7% of deaths .…”
Section: Discussionmentioning
confidence: 99%
“…The induction death was 12.3% and infection was the most important cause of death. 12 In India, septicemia was also reported to be an important cause of death, accounting for 29.7% of deaths. 13 In the multicenter report of ALL from China, non-relapse mortality during remission was 2.9% and infection was the cause of death in 73.4%.…”
Section: Discussionmentioning
confidence: 99%
“…We could not identify any source assessing which treatment protocols are used in pediatric oncology departments across each of the four jurisdictions. However, a number of clinical outcomes studies refer to the use of a range of international protocols, with or without adaptations, such as Berlin-Frankfurt-Munster, 42 , 43 Children’s Cancer Group, Children’s Oncology Group, 44 , 45 St Jude Total, 46 , 47 National Wilms Tumor Study 48 ; or national protocols (eg, in Turkey). 49 , 50 Turkey appears to be the only country in the sample where a national-level professional association (Turkish Pediatric Oncology Group) produces treatment protocols and guidelines, and conducts studies to assess their outcomes.…”
Section: Resultsmentioning
confidence: 99%